Reflection and construction of the nineteenth-century woman in Spanish and American Enlightenment - Aboal López, María (Comunicación y Género [Communication and Gender], 2019)
The press of the 19th century offers us the possibility of observing the social evolution of women in a period in which the consolidation of journalism and the appearance of the women’s press took place. Through one of the most representative illustrated magazines of the restorative period, La Ilustración Española y Americana (1869-1905), I propose to answer a question: what is it that bourgeois women read in the press of that time to become a Emma Bovary or an Ana Ozores? The woman was a new reading public that publications began to take into account. What were they exposed to as a commercial and social object?